On the credibility of threats to avoid the deployment of solar geoengineering - Michael Finus; Francesco Furini (Environmental Economics and Policy Studies, 2024)
We analyze how geoengineering in the form of solar radiation management (SRM), associated with the potential of high collateral damages, affects the governance architecture of climate agreements. We investigate under which conditions signatories to a climate agreement can avoid the deployment of SRM and implement a climate agreement on mitigation. We show that a climate agreement with all countries can be stable with the threat to deploy SRM in case a country free-rides. The threat is deterrent if collateral damages are perceived to be sufficiently high (lower threshold), but only credible if those damages are not too high (upper threshold). SRM deployment is the only threat available to signatories if they choose mitigation levels simultaneously with non-signatories (Nash–Cournot scenario). However, if signatories choose mitigation levels before non-signatories (Stackelberg scenario), an additional punishment option arises. Then if collateral damages are sufficiently large, signatories can reduce their mitigation levels and impose a heavier burden on non-signatories that would find it profitable to avoid the deployment of SRM. We show that our results are robust in two analytical frameworks frequently employed in the game-theoretic analysis of international environmental agreements.
Keywords: D71; D74; H41; Q54; 330; Coalition stability; Mitigation; Solar radiation management; Collateral damages; Credibility